(untitled) (American Journal of Islam and Society, 2000)
Native born African-American Muslims and the Immigrant Muslim community foxms two important groups within the American Muslim community. Whereas the sociopolitical reality is objectively the same for both groups, their subjective responses are quite different. Both are vulnerable to a “double Consciousness,” i.e., an independently subjective consciousness, as well as seeing oneself through the eyes of the other, thus reducing one’s self-image to an object of other’s contempt. Between the confines of culture, politics, and law on the one hand and the “Islam as a way of life” on the other, Muslims must express their cultural genius and consciously discover linkages within the diverse Muslim community to avoid the threat of double consciousness.